Association between systemic inflammation and water composition and survival in colorectal cancer - Lin, Shi-Qi; Xie, Hai-Lun; Ge, Yi-Zhong; Ruan, Guo-Tian; Zhang, Qi; Song, Meng-Meng; Zhang, He-Yang; Zhang, Xi; Li, Xiang-Rui; Tang, Meng; Shen, Xian; Song, Chun-Hua; et al. (Frontiers in Oncology, 2022)
Background: Systemic inflammation and water composition are important factors affecting cancer prognosis. This study aimed to explore the association between the neutrophil-to-lymphocyte ratio (NLR) and intracellular water/total body water (ICW/TBW) ratio and overall survival (OS) in colorectal cancer (CRC). Methods: This multicenter, prospective cohort included 628 patients with CRC between June 2012 and December 2019. The association between the covariates and OS was assessed using a Cox proportional hazards model and restricted cubic spline models. Concordance index (C-index), which integrated discriminant improvement (IDI) index and continuous net reclassification index, (cNRI) was used to compare the predictive ability of the markers. Results: The optimal cutoff values for the NLR and ICW/TBW ratio were 2.42 and 0.61, respectively. The NLR was negatively associated with OS, while the ICW/TBW ratio was positively correlated with OS. NLR ≥2.42 and ICW/TBW ratio <0.61 were both independent poor prognostic factors (hazard ratio [HR]: 2.04, 95% confidence interval [CI]: 1.44–2.88 and HR: 1.45, 95% CI: 1.04–2.02, respectively). Subsequently, we combined the two factors to construct an inflammation-water score (IWS). Patients with IWS (2, ≥1) had worse OS (HR: 2.86 and 95% CI: 1.77–4.63; HR: 1.74 and 95% CI 1.17–2.57, respectively) than those without one. Compared to its component factors, IWS score showed better predictive ability for C-index, IDI index, and cNRI. Conclusion: A high NLR and a low ICW/TBW ratio were independent risk factors for poor prognosis in patients with CRC. The combination of the two factors can provide a better prognostic prediction effect.